Membangun Kesadaran Hukum Berlalu Lintas melalui Pendekatan Komunikasi Publik - Muharrir, Muharrir; Jalaluddin, Jalaluddin; Zulfikar, Muhammad Nahyan; Munandar, Agung (Lok Seva: Journal of Contemporary Community Service, 2025)
The increasing number of motor vehicles is not always accompanied by compliance with traffic regulations, contributing to a high rate of traffic violations and accidents. This issue is not only related to technical and infrastructural aspects but also to social behavior and public legal awareness. This article aims to analyze efforts to improve traffic law awareness through a public communication approach implemented in a community service program in Gampong Ujong Tanoh Darat, Meureubo District, West Aceh Regency. The program employed an educational and communicative approach through legal counseling and interactive discussions. The materials covered the concept of legal awareness, the legal basis of traffic regulations, and types of violations along with sanctions. Evaluation was conducted qualitatively through direct observation and oral questioning during the activity involving 27 participants. The results indicate that the public communication approach enhanced community understanding of traffic law, reflected in an approximately ±20% upward trend in participants’ understanding, and encouraged a shift in compliance patterns from reactive behavior toward compliance based on internal legal awareness. The activity also demonstrated a change in community perceptions of the law, from a coercive set of rules to a shared guideline for maintaining traffic safety and order.